« Éloigner les Barabbas » - Antonin Durand (Diasporas: Circulations, Migrations, Histoire)
During the repression that followed the revolutions of 1848, the kingdom of Piedmont was considered an asylum for exiles from other Italian states. According to a tacit rule, refugees were supposed to give up any political activities in order to be tolerated. The rebellion of some Mazzinians in Milano on February 6th 1853 that involved some refugees jeopardized this fragile balance: the government felt bound to reassure its Lombard neighbor by massively expelling suspicious refugees. The aim of this article is to understand the modalities of this repression, by investigating the way refugees were selected, how they negotiated their destination, the practical conditions of their expulsion and the way they petitioned to escape it.